Development of a Model and Experimental Study of Thermal Processes in a Ferrofluid Sealer - Nesterov S.A.; Baklanov V.D. (Problems of the Regional Energetics, 2023)
The aim of the work is to create an interconnected numerical model of the magnetic, hydrody-namic and temperature fields of a ferrofluid sealer and to analyze thermal processes occurring in high-speed seals. This goal is achieved by selecting the necessary equations, boundary condi-tions, assumptions and physical properties of the magnetic fluid when building the numerical model of the sealer’s working gap, verification of the developed model by the results of the physical experiment. The important results of the work are the obtained and analyzed data on the influence both of physical properties and the geometry of the working gap of the ferrofluid sealer on the heating of the ferrofluid. With a shaft radius of 140 mm and a linear velocity at the shaft surface of 25 m/s due to viscous heating the ferrofluid temperature exceeding the ambient temperature can reach values up to 80 degrees and higher, it has been shown. The use of the equation proposed by V.E. Fertman to determine the thermal conductivity of ferrofluid and the mixing rule to determine its heat capacity allows us to describe with sufficient accuracy for en-gineering calculations the thermophysical properties of concentrated ferrofluids, it was shown. The significance of the results consists in the possibility of using the developed numerical model in the study of interrelated physical processes in the working gap of the ferrofluid sealer of ro-tating shafts. The physical and concentration parameters of the synthetic oil-based magnetic fluid given in the paper and the results of its test operation as part of a ferrofluid seal can be used to verify the results of newly developed models of ferrofluid devices.